Kegiatan Pameran Pekan Raya Cirebon (PRC) sebagai Sarana Marketing bagi Pelaku UMKM Di Kabupaten Cirebon - Istifa, Much Al khaqqoh (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Cirebon Fair (Pekan Raya Cirebon/PRC) 2025 is an exhibition and bazaar organized by the Cirebon Regency Government as a marketing platform for Micro, Small, and Medium Enterprises (MSMEs). This activity aims to increase the visibility of local products, expand marketing networks, and strengthen MSME actors’ capacity to adopt modern promotion strategies, including digital marketing. The community service methods applied include observation, interviews, pre-exhibition mentoring, and marketing strategy training. The results indicate that participants improved their skills in branding, product display, and digital media utilization, resulting in an average sales increase of 25–40% during the fair. Furthermore, PRC serves as a public educational platform to raise awareness of local products and regional culture. This activity underscores the importance of collaboration among the government, communities, academics, and MSME actors in promoting the growth of a culture-based creative economy.